Fibromatosis in Maxillofacial Region - Jawad Ahmad Kundi; Shahid Khan Khttak; Syed Murad Ali Shah; Amina Gul Mannan; Faryal Gul (Gandhara University, 2015)
SUMMARY Fibromatosis is a rare and locally aggressive benign tumor arising from musculoaponeurotic structures. They are aggressive and tend to recur. Here we present a recurrent case of fibromatosis in a nineteen year old female focusing attention on the etiology, clinical presentation, pathology, various treatment options and modes of prevention of recurrence.